Peet, R., Hartwick E. – Theories of development: Contentions, Arguments, Alternatives - Epure, Manuela (Journal of Economic Development, Environment and People, 2015)
This book review aims to discuss the new perspectives on theories of development provided by two outstanding scholars: Richard Peet and Elaine Hartwick in their recent published book “Theories of development: Contestations, Arguments, Alternatives”. An interesting point a view is presented from the beginning: development means a better life for everyone but economic growth can occur without touching problems like inequalities, poverty etc. The introductory chapter explains the differences between Growth and Development, and it is followed by a part I Conventional Theories of Development, part II Nonconventional Critical Theories of Development, part III Critical Modernism. Readers will find this book review intriguing and interesting enough to stimulate their curiosity to explore this fascinating book.